Dermal delivery of amitriptyline for topical analgesia - Kung, Chin-Ping; Sil dos Santos, Bruno; Zhang, Yanling; Hadgraft, Jonathan; Lane, Majella E.; Patel, Bhumik; McCulloch, Renée (Springer, 2021)
Amitriptyline, administered orally, is currently one of the treatment options for the management of neuropathic pain and migraine. Because of the physicochemical properties of the molecule, amitriptyline is also a promising candidate for delivery as a topical analgesic. Here we report the dermal delivery of amitriptyline from a range of simple formulations. The first stage of the work required the conversion of amitriptyline hydrochloride to the free base form as confirmed by nuclear magnetic resonance (NMR). Distribution coefficient values were measured at pH 6, 6.5, 7, and 7.4. Solubility and stability of amitriptyline were assessed prior to conducting in vitro permeation and mass balance studies. The compound demonstrated instability in phosphate-buffered saline (PBS) dependent on pH. Volatile formulations comprising of isopropyl alcohol (IPA) and isopropyl myristate (IPM) or propylene glycol (PG) were evaluated in porcine skin under finite dose conditions. Compared with neat IPM, the IPM:IPA vehicles promoted 8-fold and 5-fold increases in the amount of amitriptyline that permeated at 24 h. Formulations containing PG also appear to be promising vehicles for dermal delivery of amitriptyline, typically delivering higher amounts of amitriptyline than the IPM:IPA vehicles. The results reported here suggest that further optimization of topical amitriptyline formulations should be pursued towards development of a product for clinical investigational studies.